Evaluasi Derajat Kejenuhan Jalan Menggunakan PKJI dan VISSIM - Yasir Al Akib; Athaya Zhafirah; Greece Maria Lawalata (Jurnal Konstruksi, 2025)
A market serves as a meeting point between sellers and buyers for the exchange of goods or services, directly influencing economic activities and community mobility. The existence of a market naturally generates attraction and movement between locations, and such movements are closely tied to the use of vehicles. Human activities involving vehicle movement inevitably affect road networks and traffic flow, potentially leading to congestion. This study discusses traffic management planning along Wanaraja Street to address congestion problems caused by market activities. The research methodology includes both primary and secondary data collection. Primary data were obtained through direct surveys on traffic volume, road geometry, roadside friction, travel time, and vehicle speed. The collected data were analyzed using the Indonesian Highway Capacity Manual (PKJI 2023). Secondary data consisted of literature studies related to traffic management implementations in other locations. The VISSIM software was used to model existing traffic conditions and simulate several scenarios, including: Relocation or removal of street vendors, Modification of property access points, Road widening, and A combined scenario integrating all interventions. The simulation results are expected to provide a realistic picture of effective solutions for reducing congestion in the market area. The existing condition analysis shows a road capacity of 3,220 PCU/hour with a peak traffic volume of 2,458.4 PCU/hour, resulting in a degree of saturation (DS) of 0.76, which corresponds to Level of Service (LOS) D — indicating nearly unstable traffic flow. This study contributes to the development of urban traffic management strategies, particularly in the context of traditional market areas, by presenting simulation-based scenarios that can serve as a foundation for future transportation planning and policy-making in similar environments.